Hepatic Gi signaling regulates whole-body glucose homeostasis - Mario Rossi; Lu Zhu; Sara M. McMillin; Sai Prasad Pydi; Shanu Jain; Lei Wang; Yinghong Cui; Regina J. Lee; Amanda H. Cohen; Hideaki Kaneto; Morris J. Birnbaum; Yanling Ma; et al. (The Journal of Clinical Investigation, 2018)
An increase in hepatic glucose production (HGP) is a key feature of type 2 diabetes. Excessive signaling through hepatic Gs–linked glucagon receptors critically contributes to pathologically elevated HGP. Here, we tested the hypothesis that this metabolic impairment can be counteracted by enhancing hepatic Gi signaling. Specifically, we used a chemogenetic approach to selectively activate Gi-type G proteins in mouse hepatocytes in vivo. Unexpectedly, activation of hepatic Gi signaling triggered a pronounced increase in HGP and severely impaired glucose homeostasis. Moreover, increased Gi signaling stimulated glucose release in human hepatocytes. A lack of functional Gi-type G proteins in hepatocytes reduced blood glucose levels and protected mice against the metabolic deficits caused by the consumption of a high-fat diet. Additionally, we delineated a signaling cascade that links hepatic Gi signaling to ROS production, JNK activation, and a subsequent increase in HGP. Taken together, our data support the concept that drugs able to block hepatic Gi–coupled GPCRs may prove beneficial as antidiabetic drugs.